Assongka Bala: Interpretation of Value Systems in Handling Disease Outbreaks in the Bugis-Makassar Society - Syamsu Rijal; Syamsidar Syamsidar; Muh. Zainuddin Badollahi (Journal La Sociale, 2020)
This research is motivated by the phenomenon of pandemic disease outbreaks, treatment or prevention patterns carried out by the Bugis-Makassar community, although they have been equipped with modern knowledge about the handling of disease outbreaks, they still do some ritual outbreaks in which each of these rituals is called Assongka Bala led by a person called Sanro. This study uses a qualitative research method with a descriptive approach to describe the role of Sanro in Assongka Bala rituals, data collection techniques used are interviews and observation. This study aims to: Describe the role of Sanro in the ritual handling of outbreaks in the Bugis-Makassar community. The role of Sanro in Sanro's knowledge of ritual prevention and treatment of disease outbreaks in his community as well as knowledge of ritual management performed so that people who believe in needing a Sanro to lead the ritual. The Bugis-Makassar community, in their practice of life, is related to the social, cultural and handling of disease outbreaks, the community has a belief in the rituals of Assongka Bala which then becomes traditional values ​​that affect their knowledge about handling epidemics and also influences their behavior in maintaining health, namely the behavior system is generally divided into two types, namely in the family environment and customary environment.